Hypomagnesemia is a risk factor for nonrecovery of renal function and mortality in AIDS patients with acute kidney injury - M.S. Biagioni Santos; A.C. Seguro; L. Andrade (Brazilian Journal of Medical and Biological Research, 2010)
The objective of the present study was to determine the prevalence of electrolyte disturbances in AIDS patients developing acute kidney injury in the hospital setting, as well as to determine whether such disturbances constitute a risk factor for nephrotoxic and ischemic injury. A prospective, observational cohort study was carried out. Hospitalized AIDS patients were evaluated for age; gender; coinfection with hepatitis; diabetes mellitus; hypertension; time since HIV seroconversion; CD4 count; HIV viral load; proteinuria; serum levels of creatinine, urea, sodium, potassium and magnesium; antiretroviral use; nephrotoxic drug use; sepsis; intensive care unit (ICU) admission, and the need for dialysis. Each of these characteristics was correlated with the development of acute kidney injury, with recovery of renal function and with survival. Fifty-four patients developed acute kidney injury: 72% were males, 59% had been HIV-infected for >5 years, 72% had CD4 counts <200 cells/mm³, 87% developed electrolyte disturbances, 33% recovered renal function, and 56% survived. ICU admission, dialysis, sepsis and hypomagnesemia were all significantly associated with nonrecovery of renal function and with mortality. Nonrecovery of renal function was significantly associated with hypomagnesemia, as was mortality in the multivariate analysis. The risks for nonrecovery of renal function and for death were 6.94 and 6.92 times greater, respectively, for patients with hypomagnesemia. In hospitalized AIDS patients, hypomagnesemia is a risk factor for nonrecovery of renal function and for in-hospital mortality. To determine whether hypomagnesemia is a determinant or simply a marker of critical illness, further studies involving magnesium supplementation in AIDS patients are warranted.